Southern hemisphere atmospheric circulation: Impacts on Antarctic climate and reconstructions from Antarctic ice core data - Russell, A; McGregor, G R (Climatic Change, 2010)
The official pulished version can be accessed from the DOI below - Copyright @ 2010 Springer Verlag The atmospheric circulation patterns in the Southern Hemisphere have had a significant impact on the climate of the Antarctic and there is much evidence that these circulation patterns have changed in the recent past. This change is thought to have contributed to the warming trend observed at the Antarctic Peninsula over the last 50 years - one of the largest trends observed in this period on the planet. The trends associated with the continental Antarctic climate are less clear but are likely to be impacted less directly by atmospheric circulation changes. The circulation changes can be put into the context of longer timescales by considering atmospheric circulation reconstructions that have been performed using data from Antarctic ice cores. In this review paper we look at the main body of work examining: Antarctic climate trends; the understanding and impact of atmospheric circulation of the mid- to high-latitudes of the Southern Hemisphere; and the usefulness and reliability of atmospheric circulation reconstructions from Antarctic ice core data. Finally, beyond several of the more quantitative reconstructions, it is deemed that an assessment of their consistency is not possible due to the variety of circulation characteristics that the various reconstructions consider.